Cooperative nanoparticle H-type self-assembly of a bolaamphiphilic BODIPY derivative in aqueous medium. (16th October 2017) - Rödle, Alexander; Lambov, Martin; Mück-Lichtenfeld, Christian; Stepanenko, Vladimir; Fernández, Gustavo
Abstract: We report the H-type self-aggregation of a new linear water-soluble BODIPY bolaamphiphile equipped with amide groups and oligoethylene glycol chains. Intermolecular π-π interactions, amide-based hydrogen bonds and hydrophobic interactions lead to a highly cooperative self-assembly process. Detailed spectroscopic studies suggest that strong hydrophobic interactions are the driving force for a rotational displacement of the dye molecules within the stack in order to shield the hydrophobic π-system from water molecules. The so formed highly-ordered micellar structures have been further characterized by NMR, AFM, TEM, DLS studies and theoretical calculations. Graphical abstract: A new amide-containing bolaamphiphilic BODIPY dye has been synthesized and fully characterized. The self-assembly studies in water reveal a highly cooperative self-aggregation mechanism and the formation of micelles, driven by π-π interactions, amide-based hydrogen bonds and the hydrophobic effect. A further agglomeration of individual micelles to spherical nanoparticles is induced by CH-O interactions between the ambient hydrophilic oligoethyleneglycol chains. Highlights: A new bolaamphiphilic BODIPY derivative with amide groups and peripheral glycol chains is described. The system self-assembles in water into nanoparticle assemblies in a cooperative fashion. Spectroscopic and theoretical studies reveal a face-to-face H-type stacking of the BODIPY dyes with a twisted dye arrangement.